Structural and evolutionary analyses of the mitochondrial genome of Spuriopimpinella brachycarpa - Han, Jun; Xu, Wenbo; Yu, Huanxi; Han, Yun; Zhu, Ming (Frontiers in Plant Science, 2024)
Spuriopimpinella brachycarpa (Kom.) Kitag., a member of Apiaceae, is a perennial aromatic herb native to Northeast Asia known for its use as a culinary herb and traditional medicine. In this study, we sequenced and assembled the mitochondrial genome (mitogenome) of S. brachycarpa using second and third-generation high-throughput sequencing technologies. The genome exhibited a multi-branched structure, with a total length of 523,512 bp and a GC content of 43.37%. Annotation revealed 30 unique protein-coding genes, 21 tRNA genes, and three rRNA genes. Comparative analysis showed that the S. brachycarpa mitogenome contains several structural variations, although it shares some collinear features with other Apiaceae species. Additionally, 618 potential RNA editing sites involving C-to-U conversions were identified. We also found 59 homologous fragments between the mitogenome and plastome, comprising 8.13% of the mitogenome. These findings enrich the existing Apiaceae genome database and provide important insights into evolutionary relationships and genetic diversity.